THE ENAMEL ROUGHNESS AFTER CONVENTIONAL VERSUS AIR POLISHING: A SYSTEMATICAL REVIEW - David Tjoea; Maria Theresia Beatrix; Prajna Metta; Aldilla Miranda; Amaliya Amaliya (Universitas Baiturrahmah, 2021)
Introduction: Polishing after scaling and root planing provides a smoother tooth surface and improves patient convenience. Recently, a novel polishing system using the air-driven high-pressured device is introduced, but the advantage over conventional polishing is still questionable. This article aims to provide a comprehensive literature study regarding dental polishing by comparing the surface roughness after conventional and air polishing systems. To conduct this review, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Studies published before November 29th, 2019 were systematically reviewed under “air-polishing”, “enamel roughness”, “conventional polishing”, “scanning electron microscopy” and “10 years” publication dates files with PubMed and Google Scholar database. Review: Dental polishing assists the removal of dental plaque and stains to achieve healthy periodontal tissue. The air-polishing device cleans the deeper surface with minimal damage on enamel, the efficacy depends on handpiece degree angulation to the enamel surface, time of exposure, and the powder particle size used. The air-driven device takes a shorter working time and is easy to handle compared to conventional polishing. Prophylaxis paste in conventional polishing is abrasive, hence flattening the enamel surface. Conclusion: Both techniques show efficacy in polishing procedures, nevertheless air polishing provides a smoother surface compared to conventional devices.